Physical Activity During Pregnancy in the Prevention and Management of Gestational Diabetes Mellitus: A Narrative Review of Evidence - Bartela, Klaudia Katarzyna; Dusiel, Julia Katarzyna; Wałachowska, Anna; Tabian, Alicja; Kozłowska, Paulina; Smęt, Jakub; Chojnacka, Aleksandra Beata; Borawski, Jacek; Burdon-Sajnóg, Julia; Szymona-Kuciewicz, Zofia (Journal of Education, Health and Sport, 2025)
Background Gestational diabetes mellitus (GDM) is a common metabolic complication of pregnancy, increasing the risk of adverse maternal and neonatal outcomes and future type 2 diabetes in both mother and child. Physical activity is a key modifiable factor that may counteract pregnancy-induced insulin resistance. Aim This narrative review with elements of a systematic approach aimed to synthesize evidence (2019–2025) on the effects of physical activity during pregnancy on GDM incidence in healthy and high-risk women, and on metabolic control in women with diagnosed GDM. Material and methods A literature search was performed in PubMed, Scopus, and Web of Science for randomized controlled trials, prospective cohort studies, systematic reviews, meta-analyses, and umbrella reviews. Studies meeting predefined criteria were included for qualitative synthesis. Research results Recent meta-analyses show that regular moderate-intensity physical activity reduces GDM risk by 20–40%, particularly when started in the first trimester and totaling ≥150 minutes per week. Structured programs combining aerobic and resistance training are especially effective in women with overweight, obesity, or other risk factors. In women with diagnosed GDM, moderate exercise improves fasting and postprandial glucose and slightly lowers HbA1c, without increasing obstetric or neonatal complications. These benefits align with mechanisms such as improved insulin sensitivity, better lipid profile, reduced inflammation and oxidative stress, and enhanced placental and cardiovascular function. Conclusions Physical activity during pregnancy is a safe and effective strategy for preventing and managing GDM. Integrating evidence-based exercise recommendations into routine antenatal care, particularly for women at elevated metabolic risk, may provide a practical and cost-effective approach to reducing the growing burden of GDM and supporting long-term cardiometabolic health in mothers and their offspring.